Gap analysis of diabetes-related foot disease management systems in Pacific Islands Countries and Territories - Kay Y. Hon; Neil McMillan; Robert A. Fitridge (BMC, 2024)
Abstract Background Pacific Island Countries and Territories (PICTs) are known to have high prevalence of Diabetes Mellitus and high incidence of diabetes-related foot disease. Diabetes-related foot disease can lead to lower limb amputation and is associated with poor outcomes, with increased morbidity and mortality. The purpose of this study was to gain a better understanding of diabetes-related foot disease management in selected countries in PICTs and to identify potential barriers in management of diabetes-related foot disease management in the region. Methods A cross-sectional survey was sent to eleven hospitals across six selected PICTs. The survey instrument was designed to provide an overview of diabetes-related foot disease (number of admissions, and number of lower limb amputations over 12 months) and to identify clinical services available within each institution. Two open-ended questions (free text responses) were included in the instrument to explore initiatives that have helped to improve management and treatment of diabetes-related foot diseases, as well as obstacles that clinicians have encountered in management of diabetes-related foot disease. The survey was conducted over 6 weeks. Results Seven hospitals across four countries provided responses. Number of admissions and amputations related to diabetes-related foot disease were only reported as an estimate by clinicians. Diabetes-related foot disease was managed primarily by general medicine physician, general surgeon and/or orthopaedic surgeon in the hospitals surveyed, as there were no subspecialty services in the region. Only one hospital had access to outpatient podiatry. Common themes identified around barriers faced in management of diabetes-related foot disease by clinicians were broadly centred around resource availability, awareness and education, and professional development. Conclusion Despite the high prevalence of diabetes-related foot disease within PICTs, there appears to be a lack of functional multi-disciplinary foot services (MDFs). To improve the outcomes for diabetes-related foot disease patients in the region, there is a need to establish functional MDFs and engage international stakeholders to provide ongoing supports in the form of education, mentoring, as well as physical resources.